Canon, Value, and Cultural Heritage: New Processes of Assigning Value in the Postdigital Realm - Rodríguez-Ortega, Nuria (MDPI, 2018)
The range of modes through which the new conditions of the postdigital society is leading to a redefinition of the processes of assigning value, and the values themselves, which have hitherto prevailed in the comprehension of cultural heritage, are diverse and broad. Within this framework of critical inquiry, this paper discusses the mechanisms of canon-formation in the context of the web as the new laboratory of cultural production. It is argued that the main dynamics observed can be elucidated under the form of a triad: hypercanonization, socialdecanonization, and transcanonization. These three processes operate simultaneously interlaced and unfold in dialectical tension between the rise of the new (practices, actors, values, ideas), and the maintenance of the old (those structures that already exist). This paper delves into the paths through which such interlace dynamics and tension might reshape the principles by which canonicity develops, as well as poses open questions about the challenges facing us, which should be discussed in further studies and approaches to the problem.
Keywords: Humanidades digitales; Comunicación y cultura; Patrimonio cultural - Valoración; Canon; Postdigital culture; Cultural heritage; Digital art history